2018
DOI: 10.1371/journal.pone.0204061
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, formation mechanism, photocatalytic, cytotoxicity and antioxidant activity of sodium niobate nanocubes

Abstract: A hydrothermal method was employed to prepare the sodium niobate (NaNbO3) nanocubes. We executed time dependent experiments to illustrate the formation mechanism of sodium niobate nanocubes. It was observed that the morphology of NaNbO3 nanocubes was dependent on the reaction time and 12hr reaction time was found to be suitable. Morphology, composition, structure and optical properties of sodium niobate nanocubes were evaluated by scanning electron microscope, X-ray energy-dispersive spectrometer, X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…14 It has many technological application properties, and, among them, the photocatalytic applications presented in the literature showed excellent results. 13 13,[15][16][17][18][19][20][21][22][23] Being a promising photocatalyst because it is thermodynamically stable, has high corrosion resistance, and is nontoxic. 22,24 However, studies have shown that the natural particle shape of NaNbO 3 is cubic and presents low photocatalytic activity, but in syntheses with hydrothermal conditions followed by heat treatment, it is possible to obtain the semiconductor in the form of nanowires, with high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…14 It has many technological application properties, and, among them, the photocatalytic applications presented in the literature showed excellent results. 13 13,[15][16][17][18][19][20][21][22][23] Being a promising photocatalyst because it is thermodynamically stable, has high corrosion resistance, and is nontoxic. 22,24 However, studies have shown that the natural particle shape of NaNbO 3 is cubic and presents low photocatalytic activity, but in syntheses with hydrothermal conditions followed by heat treatment, it is possible to obtain the semiconductor in the form of nanowires, with high photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The final product was annealed further at 600 • C for 12 h to obtain pure sodium niobate nanocubes. The reaction mechanism in the formation of sodium niobate is due to orientation attached with an Ostwald ripening process as reported in the earlier works [23,24].…”
Section: Preparation Of Sodium Niobate Nanocubesmentioning
confidence: 67%
“…The MTT assay 78,79 was employed to study the cytotoxicity of ZnCo 2 O 4 /Ag 3 PO 4 nanoparticles. MCF-7, HCT116 and HFF cells were treated with various concentrations (0.0625–1.0 mg mL −1 ) of ZnCo 2 O 4 /Ag 3 PO 4 nanoparticles for 24 h as described in the Experimental section.…”
Section: Resultsmentioning
confidence: 99%
“…9 shows that in principle both semiconductor VBs can spontaneously reduce diatomic oxygen gas to produce liquid water according to 1/2O 2 (g) + 2H + (aq) + 2e À -H 2 O (l), which has a reduction potential of 1.23 V vs. NHE. However, the CB potentials are not low enough to reduce protons and release H 2 gas (2H + (aq) + 2e The MTT assay 78,79 was employed to study the cytotoxicity of ZnCo (4 mg mL À1 ). In the case of C. albicans, the minimal fungicidal concentration (MFC) value was 5 mg mL À1 (Fig.…”
mentioning
confidence: 99%